Implementasi Pengamanan Pintu Rumah Kebun Menggunakan RFID dengan Kendali Mikrokontroler - hera; Mahgiandi Fadhullah; Irwan; Limartaida Siahaan (BETRIK, 2026)
Contemporary technological advances have created a significant transformation in various aspects of life, including in the management of residences and green areas through the concept of a smart home. This study aims to design and realize an automatic door control mechanism based on a microcontroller for the garden house, with a specific emphasis on the dimension of protection and operational efficiency. In this design, RFID (Radio Frequency Identification) Technology is functioned as a property safeguard, ensuring the door can only be opened by registered individuals. This access authorization system is integrated with the Arduino Uno microcontroller to facilitate real-time protection and control functions. Furthermore, the system is also equipped with an automatic scheduling feature to control the garden house lighting (lamps), where the lighting will automatically turn on at 18:00 (6:00 PM) and turn off at 07:00 (7:00 AM) in the morning. The implementation results demonstrate effective performance and contribute to increasing both protection and convenience for users in managing access to the garden house and achieving energy savings through lighting scheduling.